2012
DOI: 10.7589/0090-3558-48.2.382
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Avian Influenza Viruses From Shorebirds: Evaluation of Surveillance and Testing Approaches

Abstract: Although influenza A viruses have been isolated from numerous shorebird species (Family: Scolopacidae) worldwide, our understanding of natural history of these viruses in this diverse group is incomplete. Gaining this information can be complicated by sampling difficulties related to live-capture, the need for large sample sizes related to a potentially low prevalence of infection, and the need to maintain flexibility in diagnostic approaches related to varied capabilities and resources. To provide information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 24 publications
4
52
2
5
Order By: Relevance
“…As a result, the sampling of AIVs within the MMF at a few sites in any given year will likely provide a snapshot of the diversity that exists within the flyway and show that movement of these viruses occurs frequently. Traditionally, this is how many very important and noteworthy North American surveillance sites operate (47,48). However, repeated annual sampling along the MMF as conducted in this study showed that, over time, the movement of these genetic lineages was often unsuccessful and resulted in a pattern of temporal structuring of the AIVs within the MMF.…”
Section: Discussionmentioning
confidence: 92%
“…As a result, the sampling of AIVs within the MMF at a few sites in any given year will likely provide a snapshot of the diversity that exists within the flyway and show that movement of these viruses occurs frequently. Traditionally, this is how many very important and noteworthy North American surveillance sites operate (47,48). However, repeated annual sampling along the MMF as conducted in this study showed that, over time, the movement of these genetic lineages was often unsuccessful and resulted in a pattern of temporal structuring of the AIVs within the MMF.…”
Section: Discussionmentioning
confidence: 92%
“…Ideally, field and laboratory efforts should yield results that accurately reflect nature—screening tests should have 100% sensitivity and specificity, and virus isolation and sequencing should not alter or bias results. However, this is rarely the case, and many studies have shown that researchers must carefully consider the limitations and biases associated with different sampling strategies and diagnostic tests [5,6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Uma possível explicação é o fato de que a primeira expedição correspondeu a uma maior amostragem de Arenaria interpres, sendo que mais da metade dos exemplares desta espécie amostrados neste estudo (23/43) foram capturados nesta saída de campo. Estes dados corroboram observações anteriores de que a prevalência de AIV em uma determinada localidade pode estar intimamente correlacionada à presença de uma espécie na qual a prevalência é particularmente elevada , como é sabidamente o caso de A. interpres (KAWAOKA et al, 1988;HANSON, 2008;STALLKNECHT;BROWN, 2008;STALLKNECHT et al, 2012).…”
Section: Reação De Inibição Da Neuraminidaseunclassified
“…Sabe-se que inúmeros fatores podem influenciar o sucesso do isolamento viral, sendo que a ausência de partículas virais viáveis e a quantidade insuficiente de vírus para causar infecção no embrião são os mais importantes a se considerar (SPACKMAN et al, 2008;STALLKNECHT et al, 2012). A caracterização das amostras isoladas revelou pertencerem ao subtipo H11N9.…”
Section: Reação De Inibição Da Neuraminidaseunclassified
See 1 more Smart Citation